ANALISIS MARGIN KONTRIBUSI SEBAGAI PERENCANAAN PENJUALAN PT.SIANTAR TOP TBK, - Putri Anjani (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
The study aims to investigate the role and significance of contribution margin analysis in the context of Siantar Top Tbk's sales planning. The results of the research show that contribution marginal analysis has become a powerful instrument in helping the management of Pt. Siantar top tbk in optimizing sales strategy. By understanding the relative contribution of each product or service, management can allocate resources efficiently, increase focus on the most profitable products, and identify areas where operational efficiency can be improved. The findings of this research make important contributions to the cost management and sales planning literature, as well as provide practical insights for corporate management in the face of complex market challenges.